Factors that Affect Share Price (Case Study on Property and Real Estate Companies Listed on the Indonesia) - Rosdiana, Riska (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to determine and analyze the Current Ratio, Debt Equity Ratio, Return on Equity on Stock Price. The population in this study were companies that Property and Real Estate on the Indonesia Stock Price for the period 2014-2016. The research design used is casual research. The sampling technique was purposive sampling method. From this method obtained 15 companies that meet the criteria during the three-year observation period. The data analysis method uses quantitative analysis. The results of the study indicate that Current Ratio has a negative and significant effect on Stock Price, Debt Equity Ratio has a positive and significant effect on Share Price, and Return On Equity has a positive and significant effect on Stock Price for those companies that Property and Real Estate on the Indonesia Stock Price for 2014-2016 period.